Theory Informed Colour Supported Instructional Design for Early Numeracy Learning in a Child with ADHD Evidence from a Single Subject Study - Lovany Marchelia Shafirarossa; Khofidotur Rofiah; Reza Akbar Fauzan (Universitas Negeri Surabaya, 2026)
Children with Attention-Deficit/Hyperactivity Disorder (ADHD) often experience difficulties in early numeracy because of deficits in attention, working memory, and executive functioning. Although flashcards are widely used to support mathematics learning, limited evidence is available regarding the effectiveness of flashcards designed according to evidence-based cognitive learning principles. This study aimed to examine the effectiveness of theory-informed colour-supported flashcards in improving early numeracy performance in a child with ADHD. A single-subject experimental design (A–B) was employed involving one eight-year-old second-grade student with ADHD attending a special school in Indonesia. The intervention consisted of colour-supported flashcards developed by integrating Executive Function Theory, Cognitive Load Theory, Dual Coding Theory, the Cognitive Theory of Multimedia Learning, and the Signaling Principle. Early numeracy performance was assessed across four baseline sessions and five intervention sessions using repeated measurements. Data were analysed through visual analysis and Percentage of Non-overlapping Data (PND). The participant's mean score increased from 63.75 during baseline to 79.00 during intervention, representing an improvement of approximately 23.9%. Complete non-overlap between baseline and intervention data (PND = 100%) indicated a strong intervention effect. These findings suggest that the observed improvement was associated not merely with repeated flashcard practice but with instructional materials intentionally designed to support attention, reduce unnecessary cognitive processing, and strengthen visual-verbal integration. The study provides preliminary evidence that theory-informed instructional design may enhance early numeracy learning for children with ADHD and offers practical implications for developing cognitively responsive mathematics instruction in inclusive and special education.